Efektifitas Penggunaan Metode Problem Solving dalam Mencapai Hasil Belajar Fisika SMP Negeri 3 Leihitu - Latukau, Randi Hasim; Edi Saputra, I Gede Purwana; Fatmalasari L, Rizky; Permana, Imam; Azmar, Azmar (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This  research  was  conducted  in  an  effort  to  improve  the  quality  of  student learning outcomes at SMP Negeri 3 Leihitu by applying the Problem Solving method.  Problem  Solving  applied  in  this  study focused  on  the  ability  of students  to  deal  with  problems  and  determine  problem  solving  solutions. Students  are  encouraged  to  be  creative,  active  and  responsive  to  problems related  to  physics  subjects,  especially  on  Forced  material.  The  type  of  this research  used  is  quantitative  descriptive  research.  The  sample  of  this  study was class VIII1students, totaling 30 students. The effectiveness of learning in this  study  can  be  known  after  analyzing  the  test  results,  namely  pre-test  and post-test.  The  effectiveness  of  achieving  student  competency  standards  was analyzed  using  the  t-test.  After  analyzing  the  data,  the  results  showed  that learning  with  problem  solving  methods  was  very  effective  because  it  was through the t-test where the thit value was 22.13 which wasobtained through the   ttab   value   of   2.042.   Meanwhile,   in   the   cognitive,   affective,   and psychomotor aspects of students with this method, it can be seen that the level of  mastery  increased  significantly  with  the  percentage  of  completeness  of 96.66%.